SOCIAL ACCOUNTING PRACTICES AND PROFITABILITY OF COMPANIES IN NIGERIA - Daferighe, Emmanuel Emeakponuzo (Archives of Business Research, 2019)
Abstract The concept of economic activity reporting is extended to include social welfare activities in which a company is to invest in and also report to its entire stakeholders. Sometimes companies are reluctant to invest in social activities because of the subjective nature of social activities which make it difficult for comparing costs and associated benefits, thus making accounting for these classes of activities complex. The motivation of this work is the claim of the stakeholders’ theorist that Social Accounting practices enhance economic benefits of companies. In this study, effort was made to examine the relationship between Health Related Cost (HRC) and Return on Equity (ROE) of companies in Nigeria. Descriptive research design was adopted in the study. Data for the study were obtained from financial report of fifteen (15) companies, that were purposively selected from Oil and Gas, Manufacturing, and Building and Construction sector of the Nigerian economy from 2009 to 2015. This resulted in 105 observations. However, descriptive statistics and multiple regression were the analytical tools adopted for the study. The hypothesis was formulated and tested using F statistic. This null hypothesis was not supported since a positive coefficient of 0.039 was obtained for the main independent variable of the study, but the relationship was not significant because F calculated (Fcal)value of 1.204 was lesser than the critical F(Ftab) value of 2.45 at 5% level of significance. It was found that Social Accounting Practices variable – HRC has insignificant positive relationship with ROE of Companies in Nigeria. It was concluded from the study that, investment in social activities has insignificant positive relationship with ROE of Companies in Nigeria; and recommended among others that, companies may cautiously support health issues that will enhance Companies’ economic benefits in the long-run. Keywords: Social Costs, Social Accounting, Social Accounting Practices, Health Related Costs (HRC), Profitability